MRI pattern in acute optic neuritis: Comparing multiple sclerosis, NMO and MOGAD - Darakdjian, Maximiliano; Chaves, Hernan; Hernandez, Jairo; Cejas, Claudia (The neuroradiology journal, 2023)
Background Several MRI findings of optic neuritis (ON) have been described and correlated with specific underlying etiologies. Specifically, optic nerve enhancement is considered an accurate biomarker of acute ON. Objective To identify differences in MRI patterns of optic nerve enhancement in certain demyelinating etiologies presenting with acute ON. Methods Retrospective analysis of enhancement patterns on fat-suppressed T1-weighted images from patients presenting clinical and radiological acute ON, treated at our institution between January 2014 and June 2022. Location and extension of enhancing optic nerve segments, as well as presence of perineural enhancement were evaluated in three predetermined demyelinating conditions. Fisher’s exact test and chi2 were calculated. Results Fifty-six subjects met eligibility criteria. Mean age was 31 years (range 6–79) and 70% were females. Thirty-four (61%) patients were diagnosed with multiple sclerosis (MS), 8 (14%) with neuromyelitis optica (NMO), and 14 (25%) with anti-myelin oligodendrocyte glycoprotein disease (MOGAD). Bilateral involvement was more frequent in MOGAD, compared to MS and NMO (43 vs 3% and 12.5% respectively, p = 0.002). MS patients showed shorter optic nerve involvement, whereas MOGAD showed more extensive lesions (p = 0.006). Site of involvement was intraorbital in 63% MS, 89% NMO, 90% MOGAD (p = 0.051) and canalicular in 43% MS, 33% NMO and 75% MOGAD (p = 0.039). Intracranial or chiasmatic involvement and presence of perineural enhancement were not statistically different between entities. Conclusion In the setting of acute ON, patients presenting MOGAD were more likely to show bilateral, longitudinally extended and anterior (intraorbital and canalicular) optic nerve involvement compared to patients with MS or NMO.